Effect of the Drying Method and Optimization of Extraction on Antioxidant Activity and Phenolic of Rose Petals - Sabrina Baibuch; Paula Zema; Evelyn Bonifazi; Gabriela Cabrera; Alicia del Carmen Mondragón Portocarrero; Carmen Campos; Laura Malec (MDPI AG, 2023)
The effect of freeze and hot air drying methods on the retention of total phenolics, antioxidant activity (AA), and color of different cultivars of rose petals was analyzed. Both methods similarly preserved the phenolic content and AA, while freeze drying showed better red color retention. Furthermore, the conditions of total phenolics and AA extraction from two rose cultivars, Lovely Red and Malu, were optimized by response surface methodology through a Box-Behnken design. The solvent exhibited a major effect on the total phenolic content (TPC) and AA. The selected parameters were ethanol 38%, 75 °C, and 30 min. Under these conditions, the predicted values for Lovely Red were 189.3 mg GA/g dw (TPC) and 535.6 mg Trolox/g dw (AA), and those for Malu were 108.5 mg GA/g dw (TPC) and 320.7 mg Trolox/g dw (AA). The experimental values were close to the predicted values, demonstrating the suitability of the model. Ultrasound-assisted extraction increased the AA of the extracts but not the TPC. Fifteen compounds were identified in the Lovely Red cultivar, with no differences between the two drying methods. The results obtained suggest that the analyzed cultivars, particularly the red ones, can be considered a natural source of powerful antioxidant compounds.